Achalasia and acromegaly: Co-incidence of these diseases or a new syndrome? - Dolina, Jiri; Kunovsky, Lumir; Kroupa, Radek; Stary, Karel; Jabandziev, Petr; Nesporova, Tereza; Maca, Karel; Andrasina, Tomas; Marek, Filip; Kala, Zdenek; Vaculova, Jitka; Said, David; et al. (Biomedical papers, 2022)
Background. Acromegaly is a disorder associated with hypersecretion of growth hormone, most usually caused by a pituitary adenoma. Dysmotility of the gastrointestinal tract has been reported in acromegalic patients. Achalasia is a disorder characterized by aperistalsis of the oesophagus with incomplete lower oesophageal sphincter relaxation and whose aetiology remains unknown. Mutations in some genes have previously been associated with the development of acromegaly or achalasia. The study aims were to analyse mutations in selected genes in a woman having both of these diseases, to identify their aetiological factors, and to suggest explanations for the co-incidence of acromegaly and achalasia. Methods and Results. A female patient with acromegaly, achalasia, and a multinodular thyroid gland with hyperplastic colloid nodules underwent successful treatment of achalasia via laparoscopic Heller myotomy, a thyroidectomy was performed, and the pituitary macroadenoma was surgically excised via transnasal endoscopic extirpation. Germline DNA from the leukocytes was analysed by sequencing methods for a panel of genes. No pathogenic mutation in AAAS, AIP, MEN1, CDKN1B, PRKAR1A, SDHB, GPR101, and GNAS genes was found in germline DNA. The somatic mutation c.601C>T/p.R201C in the GNAS gene was identified in DNA extracted from a tissue sample of the pituitary macroadenoma. Conclusions. We here describe the first case report to our knowledge of a patient with both acromegaly and achalasia. Association of acromegaly and soft muscle tissue hypertrophy may contribute to achalasia's development. If one of these diagnoses is determined, the other also should be considered along with increased risk of oesophageal and colorectal malignancy.
Keywords: acromegaly; pituitary tumour; achalasia; autoimmune syndrome; gene; mutation; AAAS; GPR101; GNAS